HSP90 stabilizes auxin receptor TIR1 and ensures plasticity of auxin responses. (4th May 2017) - Watanabe, Etsuko; Mano, Shoji; Hara-Nishimura, Ikuko; Nishimura, Mikio; Yamada, Kenji
ABSTRACT: Heat shock protein 90 (HSP90) is a highly conserved molecular chaperone that facilitates the maturation of target proteins. Here, we report that the auxin receptor TIR1 is a target of cytosolic HSP90 and that HSP90 and TIR1 form a complex. Inhibition of HSP90 compromised the nuclear localization of TIR1, and abrogated plant responses to the hormone auxin. Our findings suggest that HSP90 positively regulates auxin receptor function. We also propose that HSP90 buffers or hides phenotypic variations in animals and plants by masking mutations in some of its target proteins. Support for this proposal comes from the tir1-1 mutant of Arabidopsis, which showed a root growth defect that was only seen after inhibition of HSP90. We have developed a model in which cytosolic HSP90 works like a capacitor for auxin-related phenotypic variation via regulation of the auxin receptor in response to environmentally and genetically induced perturbations.